Milk postharvest handling practices across the supply chain in Eastern Ethiopia - Amentie, Tadele; Eshetu, Mitiku; Mekasha, Yoseph; Kebede, Ameha (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This study was conducted to assess hygienic cow milk handling practices of milk producers, traders (informal collectors, transporters and vendors) and consumers across the milk supply chain in the Eastern Ethiopia. Materials and methods: A total of 160 milk producers in Babile district were selected using multistage stratified sampling technique. Moreover, a total of 54 milk collectors and transporters (5, 40, 9 from Jigjiga, Harar and Dire Dawa town, respectively), 152 vendors (40 from Bable, Harar and Dire Dawa town and 32 from Jigjiga town) and 160 consumers (40 from each town) were selected using snowball sampling technique. Data from the selected actors were collected using focus group discussion, questionnaire survey and observations. Results: The study revealed that the majority of milk handling operations in the study area is carried out by females. The majority of respondent milk producers (87.5-92.5%), collectors and transporters (88.9-100%), vendors (77.5-90.7%) and some consumers (37.5-47.5%) performing milk handling operations were illiterate. Most of the observed actors in the study area perform malpractices (such as failure to stop milk handling while showing disease symptoms, improper hand washing and handling of risk factors) while working with milk. Majority of respondent milk producers (87.5-97.5%), all traders and some consumers (12.5-32.5%) use plastic containers for milk handling. Milk handling equipments were commonly washed using warm water, detergent and sand; however, in most case they were not properly protected from risk factors after washing. Majority of respondent milk producers (55-65%), collectors and transporters (60-66.7%), and some vendors (0-50%) and consumers (0-55%) use water from non-tap sources for hygienic practices. Conclusion: In general; the findings indicated that milk handling practices performed across the supply chain in the study area were unhygienic and therefore suggested the need for improving hygienic practices. http://doi.org/10.5455/javar.2016.c139